تقويم قانون الخدمة الجامعية رقم 23 لسنة 2008 وأثره في تقليل مظاهر الفساد الإداري والمالي: دراسة تحليلية قدية لنصوص القانون وتطبيقاته (Journal of Accounting and Financial Studies ( JAFS ), 2011)
This research includes an analytical and critique study for the version of the University Service Law No.23 for the year 2008, containing all its aspects and failure whether in its legislation or its applications.